Allergen-specific immunotherapy in children. Consensus document of the Association of Pediatric Allergologists and Immunologists of Russia (positional pаper) - Yu. S. Smolkin; O. V. Trusova; Z. A. Aliskandieva; L. Y. Barycheva; A. D. Bogomazov; K. A. Bocharova; Yu. N. Emelina; A. V. Kamaev; I. A. Larkova; A. Z. Markhaichuk; S. S. Masalskiy; N. B. Migacheva; et al. (Аллергология и Иммунология в Педиатрии, 2024)
The Document contains fundamental provisions regarding allergen specific immunotherapy in children.International clinical recommendations on the methodology were used, adapted for use in real practice.In the absence of international recommendations, the authors present the consensus opinion of the project participants, based on data from clinical studies in this area.At the moment, we bring to your attention a position paper on allergen specific immunotherapy in children, created by experts from the Association of Pediatric Allergologists and Immunologists of Russia (APAIR) based on the 2021 consensus document, with the necessary data updates.